Chomsky : ideas and ideals - Smith, N. V. (Neilson Voyne) (Cambridge University Press, 1999)
Chomsky has had a major influence on modern linguistics, psychology and philosophy. In this account of his work, Chomsky's key contributions to the study of language and the mind are analysed.
Keywords: Chomsky, Noam.; Chomsky, Noam; Linguistics.; Linguistics; Linguistique.; linguistics.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Historical & Comparative.; Linguistik; Taalwetenschap.; Electronic book.